Growing relevance of reports of adolescent cyberbullying victimization among adult outpatients - Benjamin Iffland; Lena M. Bartsch; Hanna Kley; Frank Neuner (BMC, 2023)
Abstract In the general population, prevalence rates of cyberbullying victimization have continuously increased over the past decades. However, the extent to which these increasing numbers affect clinical populations seeking treatment in outpatient services remains an open question. The present study sought to examine whether the increase of cyberbullying victimization is also reflected by increased reports of cyberbullying victimization in a clinical outpatient population. In addition, we assessed the incremental contribution of experiences of cyberbullying in the prediction of psychological symptoms when controlling for histories of childhood maltreatment and offline peer victimization. For this purpose, we analyzed routine data from N = 827 outpatients who had sought treatment at a University outpatient clinic for psychotherapy between 2012 and 2021 in a cross-sectional study design. Analyses showed that 8.3% of the patients born in the years 1980 to 2002 indicated the experience of cyberbullying victimization in their adolescence. The rate of reported cyberbullying victimization increased from 1 to 3% in patients born in the years 1980 to 1987 to 24% in patients born in the year 2000. A logistic regression revealed that patients born in the years 1995-2002 were up to nineteen times as likely to report cyberbullying victimization as patients born in the years 1980-1982. In addition, hierarchical multiple regression analyses indicated that cyberbullying victimization significantly accounted for an incremental proportion of variance (1%) in the prediction of psychological symptom distress after controlling for child maltreatment and offline peer victimization. In conclusion, this retrospective survey indicates an increase of the clinical relevance of cyberbullying victimization both in frequency of and potential contribution to etiology. Raising attention to cyberbullying in clinical care and research seems to be justified and warranted.